Realms of legal interpretation : core elements and critical variations - Greenawalt, Kent, 1936-2023 (New York, NY : Oxford University Press, 2018)
In 'Realms of Legal Interpretation', Kent Greenawalt focuses on how courts decide what is legally forbidden or authorized, and how context shapes their decisions. The problem, he argues, is that we do not, and never have, agreed on all the details of the standards United States judges should employ - like everyone else, judges have different ideas of what constitutes good common sense.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 16, 2018).
Keywords: Law -- United States -- Interpretation and construction; Law; Laws of specific jurisdictions & specific areas of law